PENGEMBANGAN MEDIA INTERAKTIF BERBASIS GAME EDUKATIF PADA MATERI NILAI – NILAI PANCASILA KELAS V SDN SAMBIREJO 1 - Aurora Alfitri Damayanti Siswanto; Frans Aditia Wiguna; Kukuh Andri Aka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This  research  aims  to  develop  an  product Interactive learning Media Based on Educational Games on Pancasila Values ​​Material .  This  research  uses  the  Research and  Development  research  method.  The  ADDIE  development  model  consists  of five  stages,  namely  1)  Analysis,  2)  Design,  3)  Development,  4)  Implementation, and 5) Evaluation. Based on the results of this research, it can be seen that the Interactive Media Based on Educational Games has an average validity value from material experts and media experts of 90% which can be said to be very valid, the practicality  value  from  the  average  practicality  value  for  teachers  and  students  is 97,1% which can be said to be very practical, the effectiveness value from the results of limited trials and extensive trials through post-test questions received a value  of  91,25%  which  means  it  is  very  effective. Interactive Media Products Based on Educational Games on Pancasila Values obtained very valid, very practical and very effective results to use.